2015
DOI: 10.1016/j.bmcl.2015.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Indirubin 3′-(O-oxiran-2-ylmethyl)oxime: A novel anticancer agent

Abstract: Indirubin is a potent inhibitor of cell cycle-related protein kinases by binding to the ATP-binding site and thus is a promising compound for development as an antitumor drug. We prepared indirubin 3'-(O-oxiran-2-ylmethyl)oxime (Epox/Ind), in which the ATP-binding site orientated part was attached by non-specific alkylating group. The IC50 value of Epox/Ind at 1.7 μM in HepG2 cells is comparable to that of cisplatin (4.0 μM). Furthermore, Epox/Ind was shown to be metabolized by a HepG2 cell lysate into indirub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Indirubin is the an active compound of Chinese herb of indigo blue, which can be used for the treatment of chronic diseases such as chronic myelogenous leukemia, and hepatitis, influenza, and encephalitis (Han, 1994;Wang et al, 2014;Gaboriaud-Kolar et al, 2015). Previous researches have shown that indirubin and its derivatives possessed many biological activities, including anticancer (Ichimaru et al, 2015;Zhang et al, 2015), anti-inflammatory (Mok et al, 2014;Kwok et al, 2016), anti-leukemia, and antivirus effects. The targets of indirubin and its derivatives have been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Indirubin is the an active compound of Chinese herb of indigo blue, which can be used for the treatment of chronic diseases such as chronic myelogenous leukemia, and hepatitis, influenza, and encephalitis (Han, 1994;Wang et al, 2014;Gaboriaud-Kolar et al, 2015). Previous researches have shown that indirubin and its derivatives possessed many biological activities, including anticancer (Ichimaru et al, 2015;Zhang et al, 2015), anti-inflammatory (Mok et al, 2014;Kwok et al, 2016), anti-leukemia, and antivirus effects. The targets of indirubin and its derivatives have been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 5-methoxyindirubin-3′-oxime (2) and 6-bromoindirubin-3′-oxime (7) inhibited the expression of the lipolysis and the lipid metabolism-related genes Atgl, Hsl, Pparα, and Ucp2, which was not significantly different from the expression levels in undifferentiated cells. Although the precise structure-activity relationships and inhibition mechanisms have not yet been clarified, these results provide new directions for designing 5-and/or 6-substituted indirubins 19,20,23) that could potentially be applied to the prevention of obesity. Further studies are warranted to elucidate the direct association between the inhibition of lipid accumulation and the structure of indirubin-3′-oximes.…”
Section: Discussionmentioning
confidence: 99%
“…16) Indirubin derivatives have also been reported to inhibit protein kinases, such as cyclin-dependent kinases and glycogen synthase kinase-3. [17][18][19][20] Our previous studies have also reported that some of these derivatives exhibit beneficial pharmacological effects, such as anti-cancer and anti-inflammatory activities. [21][22][23][24] Interestingly, indirubin-3′-oxime has been demonstrated to inhibit the differentiation of adipocytes.…”
Section: Introductionmentioning
confidence: 97%
“…We determined the antiproliferative activity to evaluate the biological significance of newly developed indirubin derivatives as anti-cancer agents. We successfully developed an effective compound (IC 50 : 1.7 μM) with anti-proliferative activity that is comparable with that of cis-platin, a powerful anticancer agent [8].…”
Section: Inhibitor Of Gsk-3βmentioning
confidence: 99%